Brain metastases of gastro-oesophageal cancer: evaluation of molecules with relevance for targeted therapies - Preusser, Matthias; Berghoff, Anna S.; Ilhan-Mutlu, Aysegül; Dinhof, Carina; Magerle, Manuel; Marosi, Christine; Hejna, Michael; Capper, David; Deimling, Andreas von; Schoppmann, Sebastian F.; Birner, Peter (Anticancer research, 2013)
Background: Brain metastases (BM) of gastro-oesophageal cancer are exceedingly rare and only limited data exist on their pathobiology. Materials and Methods: We identified tissue samples of BM of gastro-oesophageal cancer and analyzed the expression of human epidermal growth factor receptor-2 (HER2), phosphorylated signal transducer and activator of transcription-3 (pSTAT3), epithelial growth factor receptor (EGFR), V600E point mutation of the v-raf murine sarcoma viral oncogene homolog-B1 (BRAF V600E), cluster of differentiation molecule-34 (CD34), hypoxia inducible factor-1α (HIF 1-α) and Ki-67 by immunohistochemical methods. Results: Our series comprised of twenty adenocarcinomas and one oesophageal squamous cell carcinoma. Three (14%), 7 (33%), 9 (43%), 18 (86%) and 0 BM specimens were scored positively for HER2, EGFR, pSTAT3, HIF1-α and BRAF V600E expression. The median Ki-67 index was 59%. The microvascular density was moderate-to-high and active intratumoral microvascular sprouting was evident in 20/21 (95%) of BMs. The HER2 and EGFR expression status were consistent between primary tumors and BM in all three assessable cases. HIF1-α and pSTAT3 expression were significantly higher in HER2-positive cases. Conclusion: Therapeutic use of agents targeting HER2, pSTAT3, EGFR and angiogenesis may be feasible for selected BM of gastro-esophageal cancer. HER2 positivity does not seem to predispose to brain colonization in gastro-esophageal cancer.
Gesehen am 08.12.2021
keine DOI!